Analisis Bibliometrik Jurnal PARI Periode 2016-2020 - Rochani Nani Rahayu; Sobari Sobari (Central Library of Universitas Sebelas Maret, 2021)
Bibliometric analysis was carried out on PARI journal for the period 2016-2020 with the aim of knowing: 1) The number of articles published; 2) Authorization pettern; 3) Degree of collaboration; 4) The gender of the author; 5) The most productive writer; 6) The gender of writer; 7) Author’s institution; 8) The city where the author works; 9) Research topics of interest. The data sources used is the PARI journal which is downloaded from http://ejournal-balitbang.kkp.go.id/. The data recorded incuded articles, authors, agencies and cities of authors, and keywords. The were proceed using Microsof Exel 2010, and the results were presented in tabular form for discussion. The conclusion obtained is that during 2016-2020 as many as 75barticles were published, with the most articles written individually more (67 titles;89,33%), compare to article written in collaboration (8 titles; 10,67%), and the degree of collaboration is 0.11. A total of 22 female writers (57.89%) are more than 16 (14.11%) male writers. The most productive writer is Ketut Masiani who wrote 8 articles form Balai Besar Riset Budidaya Laut dan Penyuluh Pertanian, Buleleng Bali. Sekolah Usaha Perikanan Menengah Sorong is in the forst place (4;30,77%), for the category of academic institution. In the category of research institution it is known that Pusat Riset Kelautan Badan Riset dan Sumber Daya Manusia Kelautan dan Perikanan (27;43,54%). The research topics of interest include librarians, libraries, digital libraries, archives, public relations and social media